Deceptive cognates of Bikol and Visayan dialects - Fresnido, Leonora (Rivera) 1942- (1971)
The deceptive cognates of Bikol and Visayan dialects, namely, Aklanon, Cebuano, and Ilongo, were discovered and isolated. A contrastive analysis of the form, meaning, and distribution of these deceptive cognates was made. Specifically, this study aimed at lessening the difficulties of a Bikol speaker in his attempt to learn the vocabulary of the Visayan dialects.
Thesis (M.A.T.)--University of the Philippines.
Keywords: Bikol language; Bisaya language